On the Periodicity Solutions of Five Systems of Rational Systems of Difference Equations of Order Five (European Journal of Pure and Applied Mathematics, 2024)
The primary aim of this paper is to explore the behavior of several nonlinear systems of difference equations following T_{n+1}=(E_{n}E_{n-4})/(T_{n-3}(± 1 ± E_{n}E_{n-4})),E_{n+1}=(T_{n}T_{n-4})/(E_{n-3}(pm 1 ± T_{n}T_{n-4})),and obtain solution expressions for them. Moreover, we utilize MATLAB programming to simulare the dynamics and validate our results.
Keywords: : Solutions of difference equations; periodic solution; recursive sequences